Gums and stabilisers for the food industry 13 - Phillips, Glyn O.; Williams, Peter A. (RSC Pub., 2006)
The science and technology of hydrocolloids used in food and related systems has seen many new developments and advances over recent years. Gums and Stabilisers for the Food Industry 13 presents the latest research from leading experts in the field including: * Biochemical characterisation, the use of antibodies, immunostaining and enzyme hydrolysis * Chemical and physicochemical characterisation, including rheological investigation and AFM studies * Engineering food microstructure including exploiting association and phase separation in mixed polymer systems and interaction with particles * T.
Keywords: Colloids -- Congresses.; Food additives -- Congresses.; elektronické knihy; electronic books